Autograft-prosthesis composite use for a Vancouver type B1 periprosthetic femur fracture with pelvic acetabular component migration after bipolar hemiarthroplasty: A case report. (August 2019) - Ochi, Hironori; Baba, Tomonori; Tanabe, Hiroki; Ozaki, Yu; Watari, Taiji; Homma, Yasuhiro; Matsumoto, Mikio; Kaneko, Kazuo
Abstract: Introduction: Bipolar hemiarthroplasty (BHA) is a commonly performed procedure for elderly patients with an intra-capsular fracture of the femoral neck. However, surgeons performing BHA worry about the rate of acetabular wear, and acetabular prosthesis protrusion can pose a challenging surgical problem. The number of periprosthetic femur fractures is expected to increase. Generally, well-fixed stems require open reduction and internal fixation (ORIF), whereas loose stems require revision arthroplasty. Case report: A 68-year-old Asian woman was admitted to our hospital. She had sustained a left displaced femoral neck fracture at the age of 58 years. BHA was performed via a posterior approach in another hospital. Ten years later, she presented with severe left hip pain following a low-energy fall. A radiograph of the hip joint demonstrated a Vancouver type B1 periprosthetic femur fracture with severe acetabular prosthetic protrusion. Single-stage reconstructive surgery was performed. A transgluteal approach was used, with distal extension to the fracture site of the femur. Acetabular reconstruction was performed using a Kerboull-type plate in combination with massive allografts for the large bone defects of the acetabulum. Regarding the femoral side, the proximal bone fragment and cementless stem that had been fixed were longitudinally opened with an osteotomy and separated. After that, the stem was changed to a cemented long stem and combined with the prior proximal bone fragments using cement and wires in an allograft-prosthesis composite technique (autograft-prosthesis composite). Conclusion: Although the standard treatment for Vancouver type B1 periprosthetic femur fractures is ORIF, it would have been difficult to reconstruct the hip joint solely with osteosynthesis because the femur was severely shortened by marked migration of the BHA. Single-stage reconstructive surgery using an autograft-prosthesis composite was effective treatment for a Vancouver type B1 periprosthetic femur fracture with concomitant severe acetabular prosthetic protrusion after BHA.